1998
DOI: 10.1046/j.1365-3059.1998.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Combining proteolytic and phloroglucinol‐producing bacteria for improved biocontrol of Pythium‐mediated damping‐off of sugar beet

Abstract: Pseudomonas fluorescens F113 and Stenotrophomonas maltophilia W81 protect sugar beet from Pythium-mediated damping-off through production of the antifungal secondary metabolite 2,4-diacetylphloroglucinol and extracellular proteolytic activity, respectively. In this study, the two biocontrol strains were combined in a consortium, with the objective of improving upon the level of protection achieved when using each strain singly. Growth and in vitro production of 2,4-diacetylphloroglucinol by F113 and extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(60 citation statements)
references
References 40 publications
1
58
0
1
Order By: Relevance
“…In our study, the mixture of two antagonists (P. fluorescens + T. viride) suppressed Ganoderma disease development. Numerous modes of action have been postulated and demonstrated for the antagonistic effects of P. fluorescens in controlling diseases; they include synergistic effects observed on fungal pathogens with a combination of antifungal compounds (DOWLING & O'GARA 1994;DUNNE et al 1998), competition for nutrients (O'SULLIVAN &d O'GARA 1992), production of cell wall lytic enzymes (SINGH et al 1999) and induced systemic resistance (DALISAY & KUC 1995;NANDAKUMAR et al 2001). Several antibiotics have been reported to be produced by bacteria (RAAJIMAKERS & WELLER 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the mixture of two antagonists (P. fluorescens + T. viride) suppressed Ganoderma disease development. Numerous modes of action have been postulated and demonstrated for the antagonistic effects of P. fluorescens in controlling diseases; they include synergistic effects observed on fungal pathogens with a combination of antifungal compounds (DOWLING & O'GARA 1994;DUNNE et al 1998), competition for nutrients (O'SULLIVAN &d O'GARA 1992), production of cell wall lytic enzymes (SINGH et al 1999) and induced systemic resistance (DALISAY & KUC 1995;NANDAKUMAR et al 2001). Several antibiotics have been reported to be produced by bacteria (RAAJIMAKERS & WELLER 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations by other workers have shown that co-inoculation with two BCAs can either suppress the rhizosphere activity of one of the isolates or that the activity of both isolates remains unaffected. For example, Dunne et al (1998) demonstrated that the rhizosphere competence of Pseudomonas fluorescens F113 and Stenotrophomonas maltophilia W81 were essentially similar when the two strains were applied to sugar beet seed as single seed treatments or co-inoculated. In contrast, Chiarini et al (1998) reported that rhizosphere populations of a strain of Burkholderia cepacia on sorghum were suppressed by a species of Enterobacter but not by Ps.…”
Section: Discussionmentioning
confidence: 99%
“…Strains IESDV5, IESDV10, IESDV13, IESDV14, IESDV23, IESDV26, IESDV27 and IESDV28 showed higher zone of solubilization on cellulose Congo red agar media as compared to strains IESDV1, IESD2, IESD3, IESD4, IESD11 and IESD12. Dunne et al (1998) reported that the chitinase, protease, gluconase or cellulase enzymes have ability to degrade the structural matrix of fungal cell (Table 4). The enzyme catalase present in some microorganisms breaks down hydrogen peroxide to water and oxygen and helps them in their survival (McCord et al 1971;Aneja 2003).…”
Section: Biochemical Characterization Of Isolated Strainsmentioning
confidence: 99%